Design of New Potent and Selective Thiophene-Based K V 1.3 Inhibitors and Their Potential for Anticancer Activity. - Gubič, Špela; Hendrickx, Louise Antonia; Shi, Xiaoyi; Toplak, Žan; Možina, Štefan; Theemsche, Kenny M. Van; Pinheiro-Junior, Ernesto Lopes; Peigneur, Steve; Labro, Alain J.; Pardo, Luis A.; Tytgat, Jan; Tomašič, Tihomir; et al. (Cancers, 2022)
Simple Summary: In this article, we describe the discovery of a new class of potent and selective thiophene-based inhibitors of the voltage-gated potassium channel KV1.3 and their potential to induce apoptosis and inhibit proliferation. The KV1.3 channel has only recently emerged as a molecular target in cancer therapy. The most potent KV1.3 inhibitor 44 had an IC50 KV1.3 value of 470 nM (oocytes) and 950 nM (Ltk− cells) and appropriate selectivity for other KV channels. New KV1.3 inhibitors significantly inhibited proliferation of Panc-1 cells and KV1.3 inhibitor 4 induced significant apoptosis in tumor spheroids of Colo-357 cells. The voltage-gated potassium channel KV1.3 has been recognized as a tumor marker and represents a promising new target for the discovery of new anticancer drugs. We designed a novel structural class of KV1.3 inhibitors through structural optimization of benzamide-based hit compounds and structure-activity relationship studies. The potency and selectivity of the new KV1.3 inhibitors were investigated using whole-cell patch- and voltage-clamp experiments. 2D and 3D cell models were used to determine antiproliferative activity. Structural optimization resulted in the most potent and selective KV1.3 inhibitor 44 in the series with an IC50 value of 470 nM in oocytes and 950 nM in Ltk− cells. KV1.3 inhibitor 4 induced significant apoptosis in Colo-357 spheroids, while 14, 37, 43, and 44 significantly inhibited Panc-1 proliferation.